2013
DOI: 10.1271/bbb.130464
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Calcification in Aquatic Organisms

Abstract: Biomineralization is a process of mineral deposition by organisms. Calcium salts are the major component of various biominerals, calcium carbonate being the predominant type in aquatic organisms. The mechanism of biomineralization has been conventionally analyzed by microscopic observation. The findings obtained suggest that minute amounts of organic matrices in biominerals play a key role in biomineralization. We first introduced the methodology of bioactive compound chemistry into this research field. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Macromolecule-64 (OMM-64) (Tohse et al 2009) are water-soluble and acidic (due to a calcium-binding region rich in glutamate) glycoproteins involved in the control of crystal polymorphism (Nagasawa 2013). The Otolith Matrix Protein-1 (OMP-1) is another watersoluble protein required for normal otolith growth and for the deposition of another otolith protein, otolin-1.…”
Section: The Role Of Organic Matrix Composition In Otolith Biomineralmentioning
confidence: 99%
See 1 more Smart Citation
“…Macromolecule-64 (OMM-64) (Tohse et al 2009) are water-soluble and acidic (due to a calcium-binding region rich in glutamate) glycoproteins involved in the control of crystal polymorphism (Nagasawa 2013). The Otolith Matrix Protein-1 (OMP-1) is another watersoluble protein required for normal otolith growth and for the deposition of another otolith protein, otolin-1.…”
Section: The Role Of Organic Matrix Composition In Otolith Biomineralmentioning
confidence: 99%
“…The sagittae (the most studied otolith pair because of their large size) are mainly composed of calcium carbonate in aragonite form deposited on an organic matrix which represents 0.1 to 10% of total material (Degens et al 1969). The organic matrix, although present in minute amounts in otoliths, is thought to play a key role in its formation as in all biomineralization processes (Nagasawa 2013). Biomineralization of the sagittal otolith (referred to as "otolith" hereafter) is an acellular process that takes place in the saccule (otic sac).…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that miR-71 directly targeted the cap-1 gene and miR-13b-regulated knickkopf gene expression. As reported, cap-1 and knickkopf genes are involved in chitin synthesis (33)(34)(35). Chitin is crucial in the innate immunity of animals.…”
Section: Discussionmentioning
confidence: 78%
“…This was supported by a more recent study by Gal et al who reported that soluble, negatively charged polysaccharides were an essential foundation for calcite crystals to form in the correct location [26]. Three acidic polysaccharides, termed PS-1, -2 and -3, have been identified in coccolith plates of P. carterae [13]. These biomacromolecules are hypothesised to be synthesised in the golgi (the coccolith vesicle), forming the template [10,24].…”
Section: Coccolithophore Organicsmentioning
confidence: 83%
“…However, a recent study by Durak et al has reported that Noelaerhabdaceae and Pleurochrysidaceae coccolithophore families have evolved to mineralise without silica [12]. Calcification in coccolithophores [13] is a distinctly different process to silicification in diatoms [14]. The cellular processes that underpin both these mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%